Exercício resistido progressivo em mulheres com osteoartrite de joelhos: ensaio clínico randomizado e controlado - Jorge, Renata Trajano [UNIFESP] (2011)
Background: Knee osteoarthritis (OA) is a common musculoskeletal disorder. Recent guidelines for the management of knee OA emphasize the role of strengthening exercises. While most studies focus on the benefits of quadriceps strengthening, little is known about hip strengthening exercises in knee OA and also, about prescription in terms of intensity, duration, frequency and load. Objectives: To assess the effectiveness of a a progressive resistance exercise program (PREP) on pain, function, quality of life, walking endurance and muscular strength in women with knee OA. Methods: Eligible patients included women, age 40-70 years old with pain between 3 and 8 on a 10-cm pain scale. Of the 144 patients screened, 60 met the eligibility criteria and were randomized to the Experimental Group (EG) or Control Group (CG). Patients in EG participated in a 12-week PREP twice a week and CG remained on a waiting list for physiotherapy. The PREP consisted of strengthening exercises for knee extensors, knee flexors, hip abductors and hip adductors, all performed with 50% and 70% of the maximum amount of weight that can be tolerated for a given exercise (1 repetition maximum-1RM) using machines with free weights. The resistance was reevaluated every 2 weeks. Assessment for pain (VAS), function (WOMAC), quality of life (SF-36), muscle strength (RM) and walking endurance (6MWT) were done at baseline, 6 weeks and 12 weeks by a blinded assessor. Results: 29 female patients were randomly assigned to the EG and 31 to the CG. In the comparison between groups using ANOVA for repeated measures, we found better results for the EG with statistical difference for VAS (p<0.001), WOMAC (pain: p < 0,001; function: p < 0,001 and aggregate score: p<0.001), some domains of SF-36 (physical function: p=0.002 ; physical role limitation: p=0.002 and pain: p =0,044) and on muscular strength (extensors: p<0.001; flexors: p=0,002 and abductors muscles: p<0.001). At 6 weeks, there was a significant statistical difference in the pain VAS (EG: 5.9; CG:7.0; p=0.022); the WOMAC (EG: 30.9; CG:39.1; p=0.017); SF-36 physical component summary (EG:39.1; CG:30.3; p=0.045) as well on muscular strength of knee extensors (EG:10.4; CG:5.7; p<0.001); knee flexors (EG:7.4; CG:5.2; p=0.003) and hip abductors (EG:29.2; CG:21.0; p<0.001). At 12 weeks, there was a statistically significant difference in the pain VAS (EG: 4.3; CG: 6.6; p<0.001); the WOMAC (EG:24.1; CG: 38.3; p<0.001); SF-36 physical component summary (EG: 49.8; CG: 30.8; p=0.000); physical role limitation (EG: 48.3; CG: 16.9; p=0.001) and pain (EG: 58.6; CG: 41.7; p=0,006); as well on muscular strength of knee extensors (EG: 11.8; CG: 5.7; p=0.000), knee flexors (EG: 8.6; CG: 5.3; p=0,000) and hip abductors (EG: 32.7; CG: 19.5; p=0.000). Conclusion: The PREP was effective in reducing pain, improving function, some domains of quality of life and strength in women with knee osteoarthritis.